Necessary and sufficient optimality conditions for fractional interval-valued variational problems - Rayanki, Vivekananda; Kummari, Krishna (Yugoslav Journal of Operations Research, 2023)
In this paper a special kind of variational programming problem involving fractional interval-valued objective function is considered. For such type of problem, insights into LU optimal solutions have been discussed. Using the LU optimal concept, we established optimality conditions for the considered problem. Further, We formulated a Mond-Weir dual problem and discussed appropriate duality theorems for the relationship between dual and primal problems.